A NiCo/NiO–CoOx ultrathin layered catalyst with strong basic sites for high-performance H2 generation from hydrous hydrazine. Issue 17 (15th April 2016) - Wu, Dandan; Wen, Ming; Lin, Xijian; Wu, Qingsheng; Gu, Chen; Chen, Hanxing
Abstract : The NiCo/NiO–CoO x ultra-thin layered catalyst exhibits high-performance towards H2 generation from N2 H4 ·H2 O without alkali as a catalyst promoter at 25 °C. Abstract : The exploration of non-noble-metal recyclable catalysts for high efficiency H2 generation from N2 H4 ·H2 O is of great significance for the sustainable strategy of society. A NiCo/NiO–CoO x ultrathin layered catalyst was fabricated successfully via a dynamics controlling coprecipitation–reduction (DCCR) process followed by calcination and applied to H2 generation from N2 H4 ·H2 O. Small nanosized NiCo particles (∼4 nm) were uniformly anchored on the surface of the NiO–CoO x ultrathin layered supports. Based on the cooperation between the NiCo active-centers and high intensity base-sites of the NiO–CoO x support, the Ni70 Co30 /NiO–CoO x ultrathin layered nanocomposite exhibits over 99% selectivity for H2 generation from N2 H4 ·H2 O with a high reaction rate (molN2 H4 molNiCo −1 h −1 ) of 5.49 h −1 without using alkali as a catalyst promoter at 25 °C, which is superior to the reported studies. Moreover, the NiCo nanoalloys loading on the NiO–CoO x sheets enables an outstanding recycle performance over 10 cycles. The non-noble-metal NiCo/NiO–CoO x layered nanocomposite shows great value in catalyzing H2 generation from N2 H4 ·H2 O in practical applications.